The Indirect Impact of Smallholder Vegetable Production on Children's Nutrition Outcomes in Rural Vietnam - Genova, Christian; Umberger, Wendy; Peralta, Alexandra; Newman, Suzie; Zeng, Di (Frontiers in Sustainable Food Systems, 2022)
Childhood undernutrition, particularly stunting, wasting, and micronutrient deficiencies, remains a major health concern in rural Vietnam. While literature suggests leveraging agriculture to improve child nutrition via agricultural diversification, market engagement, and women’s empowerment, very few studies have empirically explored how smallholder vegetable production can influence household nutrition. This paper examines the association of household-level vegetable diversity, market access, and market participation with nutrition outcome measures of children in smallholder households. We use a cross-sectional household dataset, collected in 2016 in northwest Vietnam, covering 234 children aged 6-60 months. We estimate and compare the results of regression models using three-stage least squares (3SLS), ordinary least squares (OLS), logistic regression, and seemingly unrelated regression (SUR), to explore variations in six nutrition outcome measures: height-for-age z-score (HAZ), weight-for-height z-score (WHZ), weight-for-age z-score (WAZ), stunting, wasting, and underweight. Our results suggest smallholder vegetable production has a significant indirect association with children’s nutrition status via market participation. Market participation is an important factor in improving girls’ HAZ and WHZ, and in reducing the probability of boys being stunted and underweight. The additional income from selling vegetables allows households to purchase nutritious food, which is likely to have a positive impact on children’s nutrition outcomes.